Travelling in a Cosmopolitan Milieu: An Intercultural Exchange of Two Artists as Educators in Conversation at a UK University - Hayward, Beverly (International Journal for Talent Development and Creativity, 2022)
By travelling in a cosmopolitan milieu in a UK university, pedagogies of possibilities are explored. Over a period of five years the exploration narrates the journeys of, what Clover (2010) calls, “artists as educators,” documenting conversations and creative pedagogic practises. This is despite the closure of the university campus in 2023, due to an overt neoliberal agenda. The findings of two feminist cosmopolitans in conversation, illustrates that when stories require repetition, that is the retelling of a certain narrative as well as stories that are whispered, they are of a particular significance. Represented are resistance, resilience and rebellion. In addition to the tone and context of conversations being important, the findings in the research suggest that by adhering to a feminist cosmopolitan ontology, encouraged is a sensitive, ethical encounter with others. This approach suggests that those marginalised in the academy and the artworld, then are seen and heard. Their voice and artwork are visualised as challenges to the norms of the academy.